THE METHODOLOGICAL UNIT OF SCIENTIFIC RESEARCH IN TERMS OF CONCEPTUALISATION OF PEDAGOGICAL KNOWLEDGE - Alfia F. Zakirova (Russian State Vocational Pedagogical University, 2015)
Aim. The contents and structure of the methodological unit ofscientific research on educational problems are defined. The present study is the continuation of methodological articles cycle appealed to support the work of newcomer researchers.Methods. The requirements to research justification are disclosed; logicstylistic and language features of the argument while designing the methodological unit are described from the standpoint of complete, panoramic and hermeneutic approaches.Results and scientific novelty. The characteristic of research hypotheses types and the functions realized by them is given. The scientific hypothesis is presented as the instrument of trans-level conceptualization of pedagogical knowledge. The author's interpretation of a «through» stage-by-stage hypothesis-generating as process of a meaning-making and theoretical organization of research object is offered. Dual character of the hypothesis-generating is presented; it integrates logic-gnoseological and valuable-conceptual, rational and intuitively figurative principles. Typical mistakes in formation of the methodological research unit are analysed. The directions of a multiangle reflection implementation in the course of research activity are designated.Practical significance. The recommendations proposed in the study can by used by teachers-researchers, students, undergraduates, graduate students and doctoral candidates mastering practical methodology of scientific and pedagogical search; and also the materials are designed for research supervisors motivated to increase efficiency and tutorial activity content.